Chicago Shakespeare Theater : suiting the action to the word - Buccola, Regina, 1969-; Kanelos, Peter, 1969- (Northern Illinois University Press, 2015)
"Chicago Shakespeare Theater is widely known for vibrant productions that reflect the Bard's genius for intricate storytelling, musicality of language, and depth of feeling for the human condition. Affectionately known to natives of the Windy City as 'Chicago Shakes, ' and now in its twenty-fifth season, this vanguard of Chicago's rich theatrical tradition celebrates its silver anniversary with this ... collection of original essays by world-renowned scholars, directors, actors, and critics"--